Literature Review: The Effectiveness of Risk Management Training in Financial Institutions in the Digital Era - Rangga Adhitia Hermawan; Pajar Pajar; Avivah Sri Handayani; Shella Meylani; Niken Intan Pratiwi; Yesie Handayani; Masno Marjohan (International Journal of Economics, Management and Accounting (IJEMA), 2025)
The rapid development of digital technology has significantly changed the landscape of the financial industry. The digitisation of financial services offers convenience and efficiency, but also brings new challenges in terms of risk. Effective risk management is key to ensuring the stability and sustainability of financial institutions in the digital age. The method used is a literature study taken from several national journals and expert articles accessed online. This method aims to summarise the current understanding of a topic. The literature review presents previously published material and analyses new facts. Digital financial risk management strategies in retail companies require a comprehensive, adaptive, and technology-based approach. The digital financial sector faces increasingly complex risks as technology adoption accelerates. There are several challenges and threats in risk management for financial institutions in the digital era, one of which is technological advancement. The emergence of increasingly sophisticated technology has a significant impact on the structure of life. Digital financial risk management requires adaptive technology-based strategies to address complex risks in the digital era. The roles of AI, blockchain, and IoT are key in risk mitigation. Financial institutions, including Islamic and conventional banks, need to enhance regulatory compliance, digital literacy, and service innovation to compete with fintech companies and sustain customer trust.